Implementasi Nilai-Nilai Kebangsaan Bersumber UUD 45 dan NKRI Pada Peran Manajemen Sekuriti Guna Meningkatkan Kesadaran, Keamanan Data Pribadi Media Sosial Instagram - Naomira, Allysa Devia; Soesanto, Edy; Vilani, Laurencia (Media Hukum Indonesia (MHI), 2024)
In the digital era which is increasingly developing rapidly, information technology and the internet have revolutionized the way humans communicate. One of the impacts is the emergence of social media as the main platform for interacting and exchanging information. Social media such as Instagram has become an inseparable part of human life. This platform is not only a means of obtaining information, but also a forum for sharing and disseminating information to a wide audience. However, easy access to information on social media, including personal data and privacy, opens up opportunities for abuse. This needs to be taken care of so that interactions on social media are safe and avoid danger. Personal data is an important element of human rights, closely tied to personal rights and the right to privacy. This is confirmed in the 1945 Constitution and human rights principles which guarantee security for every individual. In Indonesia, personal data protection is still weak, the personal data law has just been enacted in Law no. 27 of 2022 concerning Personal Data Protection. as one source of leakage of personal data information due to low awareness of users regarding personal data security. This is made worse by the lack of education and training from Instagram.